2019
DOI: 10.1002/celc.201900524
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic Deposition of Tin Sulfide Nanocubes as High‐Performance Lithium‐Ion Battery Anodes

Abstract: We report the use of assemblies of SnS nanocubes as lithium‐ion battery anodes. The particles are deposited in dense, conductive thin films with high gravimetric capacity using electrophoretic deposition, negating the requirement for binders or conductive additives. Although SnS nanocube ensembles display both alloying and conversion modes, a significant benefit to capacity retention during long‐term cycling was observed by limiting the upper cutoff voltage to 1 V. In this alloying‐only regime that is more rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 69 publications
0
27
0
Order By: Relevance
“…[33,34,36] Until now, a number of approaches have been employed to synthesize the 0D SnS nanomaterials with narrow size distribution. [31,[42][43][44][45][46][47][47][48][49][50] For example, in 2010, Ning et al [47] reported 0D SnS NPs by a solvothermal method using Sn 6 O 4 (OH) 4 as a Sn source and TAA as a S source. By strictly controlling the molar ratio of Sn to S, the 0D SnS NPs with uniform distribution can be obtained, as shown in Figure 2a.…”
Section: Synthesis Of 0d Sns Nanomaterialsmentioning
confidence: 99%
See 3 more Smart Citations
“…[33,34,36] Until now, a number of approaches have been employed to synthesize the 0D SnS nanomaterials with narrow size distribution. [31,[42][43][44][45][46][47][47][48][49][50] For example, in 2010, Ning et al [47] reported 0D SnS NPs by a solvothermal method using Sn 6 O 4 (OH) 4 as a Sn source and TAA as a S source. By strictly controlling the molar ratio of Sn to S, the 0D SnS NPs with uniform distribution can be obtained, as shown in Figure 2a.…”
Section: Synthesis Of 0d Sns Nanomaterialsmentioning
confidence: 99%
“…With respect to the electrochemical performances in batteries, although pure SnS nanostructures, such as 0D SnS NPs, [31] 1D SnS nanostructures, [62,66] 2D SnS NSs or nanoplates, [153,184,185] 3D SnS nanoflowers or yolk-shell microstructures, [32,99,186] have made considerable progress in the field of batteries, such as Li or Na-ion batteries and Li-S batteries, yet its low electronic conductivity, large volume expansion and poor cycling stability during charging and discharging, greatly limit its practical applications. To this end, a number of researches has focused on the functionalization of SnS with graphene, [69,101,124,137,158,159] CNTs, [111,112,156,187] C fibers, [28,30,146] conductive polymers, [138] MoS 2 NSs, [116,147,150] etc., to achieve outstanding electrochemical performances.…”
Section: Batteries and Solar Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this process, the properties of deposits can be controlled by parameters related to the electric field and suspension. EPD provides a fast fabrication process which is cost-effective, suitable for mass production, and flexible to be used for substrate with different shapes, while preparing a stable suspension with sufficient particle surface charge and controlling possible side reactions are factors that might limit its abundant use. Although there has been research studies regarding exploiting EPD for electrode fabrication in energy storage, they mostly have been only focused on the deposition of a single component rather than multicomponents or using surfactant binders to tune the surface charge of the particles …”
Section: Introductionmentioning
confidence: 99%